Disease occurrence and fruit quality of pre-harvest calcium treated red flesh dragon fruit (Hylocereus polyrhizus) - Abdul Ghani, Muhd Azlan; Awang, Yahya; Sijam, Kamaruzaman (Academic Journals, 2011)
A study aiming at increasing Ca content in red flesh dragon fruit (Hylocereus polyrhizus) via pre-harvest fruit CaCl2 spray in relations to postharvest disease occurrence and fruit quality parameters was conducted. From day 7 after anthesis, red flesh dragon fruits (H. polyrhizus) were sprayed at weekly interval for four times with different concentration of CaCl2 (0, 1, 2, 3, and 4 gl-1). Fruit Ca content in fruit peel (DW basis) were markedly increased with the increasing Ca concentration in the applied solution but the Ca application did not affect Ca content in flesh. The compositions of N, P, K and Mg were not affected by the treatment. The severity of anthracnose and brown rot, caused by Colletotrichum gloeosporioides andMonilinia fructicola, respectively, of artificially wounded fruits was reduced in pre-harvest CaCl2-treated fruits. The concentrations of soluble solids and titratable acidity in fruit were not affected by the treatment. The firmness of fresh cut fruit was markedly enhanced at higher concentration of CaCl2. Beneficial effects of increasing Ca in fruit can be seen in the increase of fruit firmness although this did not contribute in enhancement of fruit quality-related parameters. Increased Ca content in treated fruits, together with no effects of treatment on other mineral nutrients, increased the ratio of Ca to other elements and this may contribute directly to the reduction of anthracnose and brown rot severity in CaCl2-treated fruits.